2016
DOI: 10.1016/j.jor.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The clinical implications of heterotopic ossification in patients treated with radial head replacement for trauma: A case series and review of the literature

Abstract: Radial head arthroplasty (RHA) is an acceptable treatment for comminuted radial head fractures (RHF). Fourteen patients with no postop HO prophylaxis were treated with RHA for comminuted RHF. A 50% incidence in HO was seen following RHA with a statistically increased risk (p ≤ 0.05) of reoperation compared to those without HO. Decreased ROM was seen on the affected side (p ≤ 0.05); patients without HO showed no statistical difference (p ≥ 0.05) in ROM or grip strength. HO following RHA increases patient risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Heterotopic ossification is a frequent complication associated with post-traumatic healing in clinical conditions such as fractures, spinal cord injury, traumatic brain injury, blast injuries, severe burns, and extensive surgeries, such as hip arthroplasty, acetabular, and elbow surgeries. 14 In addition to trauma-induced localized HO as described above, this pathological phenomenon is also seen systemically in a rare genetic disorder, ‘Fibrodysplasia Ossificans Progressiva’ (FOP), where heterotopic bone forms in soft tissues and joints, either sporadically or in response to an external trauma. 5 Interestingly, in both nongenetic and genetic cases, this bone forms at sites with a high concentration of connective tissue cells (perimysium, periosteum, peritenon) and entheses.…”
Section: Trauma-related Ho: Definition and Epidemiologymentioning
confidence: 99%
“…Heterotopic ossification is a frequent complication associated with post-traumatic healing in clinical conditions such as fractures, spinal cord injury, traumatic brain injury, blast injuries, severe burns, and extensive surgeries, such as hip arthroplasty, acetabular, and elbow surgeries. 14 In addition to trauma-induced localized HO as described above, this pathological phenomenon is also seen systemically in a rare genetic disorder, ‘Fibrodysplasia Ossificans Progressiva’ (FOP), where heterotopic bone forms in soft tissues and joints, either sporadically or in response to an external trauma. 5 Interestingly, in both nongenetic and genetic cases, this bone forms at sites with a high concentration of connective tissue cells (perimysium, periosteum, peritenon) and entheses.…”
Section: Trauma-related Ho: Definition and Epidemiologymentioning
confidence: 99%
“…19 Assessment included the position of the stem for the stemmed components which was considered to be valgus or varus when the distal extremity apposed the lateral or medial aspect of the radial cortex, respectively, signs of periprosthetic osteolysis (Fig. 2), heterotopic ossification according to the Brooker classification, 35,36 and capitellar wear. These were noted at each post-operative review.…”
Section: Figmentioning
confidence: 99%
“…The occurrence of HO was reported at the variable rate following the radial head replacement. 19,20,43 Bowman et al observed that the patients who developed HO after radial head replacement had a statistically significant postoperative ROM deficits. 43 In our study, one of the patients who developed HO had restricted forearm pronation.…”
Section: Discussionmentioning
confidence: 99%